2016
DOI: 10.1177/1473325015617233
|View full text |Cite
|
Sign up to set email alerts
|

“How do I do Discourse Analysis?” Teaching Discourse Analysis to novice researchers through a study of intimate partner gender violence among migrant women

Abstract: This article will examine how Discourse Analysis can be taught and used. Specifically, it will first explore how to introduce the basic theoretical and epistemological principles of Discourse Analysis and how these dimensions must be taken into account when students start doing Discourse Analysis. Next, the article will illustrate the basic steps of Discourse Analysis through a research project. We focus our attention on the process of teaching and learning Discourse Analysis using a study of intimate gender v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Studies assessing biomedical and psychosocial perspectives in various texts on ADHD have mostly applied discursive analytic techniques. They start from the crucial assumption that information provided in psychoeducational materials mirrors the discourse around ADHD, while simultaneously constructing that same discourse [22][23][24]. Previous studies have often found the biomedical perspective to be overrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing biomedical and psychosocial perspectives in various texts on ADHD have mostly applied discursive analytic techniques. They start from the crucial assumption that information provided in psychoeducational materials mirrors the discourse around ADHD, while simultaneously constructing that same discourse [22][23][24]. Previous studies have often found the biomedical perspective to be overrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the data followed a discourse analysis approach over four phases (Carbó, Andrea Vázquez Ahumada, Caballero, Lezama Argüelles, & Drisko, 2016). After reading the transcripts carefully several times, the transcripts were coded as we looked for patterns, variability, and differences in the content in each meeting which provided indications to turning points overtime.…”
Section: Discussionmentioning
confidence: 99%
“…Gee, 2011;Johnstone, 2017;Paltridge, 2008;Tannen et al, 2015) és rövidebb, könnyebben feldolgozható cikk, útmutató érhető el (pl. Adolphus, é. n.;Carbó et al, 2016). A diskurzuselemzés elmélete a posztmodern társadalomelmélet bonyolult kérdéseihez vezet el, a kutatásmódszertani gyakorlata pedig szintén meglehetősen változatos.…”
Section: Jogi Diskurzusok Kritikai Elemzéseunclassified